Thermal characterization of silver-based conductive polymers for flexible electronics / Zuraihana Bachok ... [et al.] - Bachok, Zuraihana; Saad, Abdullah Aziz; Zulfiqar, Sana; Abas, Aizat; Marzuki, Marina (Penerbit UiTM (UiTM Press), 2025)
Conductive polymer composites are increasingly important due to their unique electrical and polymeric properties, with applications in flexible electronics and sensors. Understanding their thermal behavior especially in PDMS-OH with silver (Ag) nanoparticles, is essential for optimizing performance and reliability. This study investigates the thermal behavior of conductive polymer composites made from polydimethylsiloxane with hydroxyl end groups (PDMS-OH) and varying contents of silver nanoparticles (40%, 60%, and 80%) using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The DSC result revealed that the 60% silver content offers an optimal balance between flexibility and processability, with a Tg of approximately 178.13°C and a delta Cp of 130 J/g°C. Meanwhile, TGA results indicate that the 60% silver conductive polymer also achieves superior thermal stability and minimal degradation, making it the most suitable choice for high-performance applications. Although increasing the silver content can improve thermal stability, excessive silver content may lead to adverse effects. Therefore, the PDMS-OH conductive polymer with 60% silver content emerges as the optimal formulation, providing a favorable combination of flexibility, processability, thermal stability, and minimal weight loss, outperforming both the lower and higher silver content formulations, which can lead to more durable and efficient electronic components, enhancing the overall quality and lifespan of the end products.